2017
DOI: 10.1590/0103-8478cr20160924
|View full text |Cite
|
Sign up to set email alerts
|

DiseasePlan - a spreadsheet application for training people to assess disease severity and to assist with standard area diagram development

Abstract: Several computer applications have been proposed for the visual assessment of plant disease severity; however, they have some restrictions such as not permitting the user to make modifications. Therefore, the VBA-Excel application was developed as a means to train people to estimate disease severity and to validate standard area diagrams through images and disease severity values (percentage, rating or score) inserted into a database. The main performance statistics are screen displayed and spreadsheet recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…However, training raters may result in a standardized evaluation, reducing the observed discrepancies and consequently increasing the reliability of the estimates among pairs of raters. Various studies have demonstrated the relevance of training to increase performance, especially for the less experienced raters (González-Dominguez et al, 2014;Bock et al, 2016;Sachet, Citadin, Danner, Guerrezi, & Pertille, 2017). Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, training raters may result in a standardized evaluation, reducing the observed discrepancies and consequently increasing the reliability of the estimates among pairs of raters. Various studies have demonstrated the relevance of training to increase performance, especially for the less experienced raters (González-Dominguez et al, 2014;Bock et al, 2016;Sachet, Citadin, Danner, Guerrezi, & Pertille, 2017). Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…OLS images (228 pictures), of known severity, were inserted into the Disease Plan spreadsheet, which performs the randomization of images, estimate recording and agreement statistics (SACHET et al, 2016). The precision, accuracy, deviations from the ideal projection, Lin`s concordant correlation coefficient as shown by NICOLI et al (2015) and the smallest difference detectable value based on the random effect of the one-way ANOVA corresponding to the least significant difference (DMS-t com P=0.05) were evaluated.…”
Section: Crop Protectionmentioning
confidence: 99%
“…Interestingly, the development of these computer programs in the 1980s and 1990s was not immediately followed by computerized systems with greater sophistication to draw more realistic symptomatic digital leaves, despite the advances in software engineering. Indeed, there have been very few training programs developed since (Aubertot et al 2004;Sachet et al 2017).…”
Section: Arrival Of Personal Computers and Programs To Aid In Assessment Trainingmentioning
confidence: 99%
“…The inexpensive availability of scanners and portable digital cameras in the early 2000s, and the development of plant disease-specific image analysis software facilitated development of SADs (Del Ponte et al 2017 (Sachet et al 2017).…”
Section: Establishment and Evolution Of Sads Researchmentioning
confidence: 99%